Human Resources Management Practice and Firm Performance in the Nigerian Oil and Gas Industries - Ekwutosi, Ozims; Chukwubuike, Alugbuo Cosmas (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
The study explores the relationship between human resource management (HRM) practices and firm performance in the Nigerian oil and gas industry, addressing a critical gap in understanding how staff orientation impacts organizational outcomes. Despite extensive research on HRM, limited attention has been given to its influence on employee retention, customer retention, and productivity in this sector. Using a survey of 714 HR professionals and managers, the research identifies significant correlations between effective staff orientation and enhanced employee retention, which subsequently improves customer retention and productivity. These findings underscore the importance of comprehensive orientation programs, employee-focused strategies, and continuous HRM evaluation to boost firm performance. The study provides valuable insights for practitioners and policymakers, emphasizing the need for customer-centric cultures and robust HRM practices to drive organizational success.